Environmental degradation and ecological resilience in arid ecosystems of Naâma (Algeria): A multi-index assessment over four decades - Guerine, Lakhdar; Bendouina, Naîmi; Bourahla, Lame (Brawijaya University, 2025)
Over four decades (1984-2024), Naâma's arid ecosystems exhibited alarming environmental degradation, with climate trends showing a significant SPEI decline (-0.4 annually, p<0.001), indicating intensified drought, while land surface temperature surged by +3.5 °C (+0.085°C/year, p<0.001) 2.1 times faster than global warming rates. The Aridity Index rose (+0.0003/year, p = 0.002), confirming accelerated aridification, with a critical tipping point detected in 2000. Vegetation dynamics mirrored this crisis: NDVI declined significantly across all municipalities (-0.002/year, p<0.001), most severely in Asla (-0.0030/year) and Djenien Bourezg (-0.0028/year), while NDVI-based water stress (NDWI) also dropped (-0.0004/year, p<0.05). Only soil-adjusted SAVI showed relative stability, suggesting limited soil adaptation. Ecological resilience varied starkly among municipalities, with Kasdir and Mekmen Ben Amar demonstrating higher resistance (R = 0.15-0.18) and shorter drought recovery (1.5 years), contrasting with Asla and Djenien Bourezg’s vulnerability (R = 0.06-0.07) and prolonged recovery (3.8 years). The Synthetic Environmental Index (SEI) quantified this hierarchy: Asla and Djenien Bourezg faced critical degradation (SEI<-1.2), driven by thermal stress (LST weight: 0.28) and aridity (AI weight: 0.22), while Kasdir and Mekmen Ben Amar maintained moderate conditions (SEI>-0.5). All municipalities except Mekmen Ben Amar showed significant SEI declines, with Naâma’s degradation rate 2.3 times faster than the Mediterranean Basin, underscoring the urgent need for targeted restoration within Algeria’s Green Dam initiative.